2016
DOI: 10.3233/bd-160238
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic revelation and outcome of the surgical management of idiopathic granulomatous mastitis; An Egyptian centre experience

Abstract: History of breast feeding together with early failure of complete nursing from a single breast is the most important risk factors for development of IGM in young aged women. Surgery plays an important role in treating IGM, however, it should be directed towards excision of the present mass (s) together with the pathological and colonized duct system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…GM is per definition a sterile inflammatory disease; therefore, antibiotic therapy usually fails [30,31] (table 1). …”
Section: Treatmentmentioning
confidence: 99%
“…GM is per definition a sterile inflammatory disease; therefore, antibiotic therapy usually fails [30,31] (table 1). …”
Section: Treatmentmentioning
confidence: 99%
“…As the infection is presumed based on physical exam findings, antibiotic therapy is usually initiated without microbiological proof. GM is by definition a sterile inflammatory disease; therefore, antibiotic therapy usually fails [ 8 , 9 ]. This would explain the lack of success with the initial pharmacotherapy.…”
Section: Discussion/commentarymentioning
confidence: 99%
“…[139], IdGM involved fewer than 2% of benign breast conditions. The prevalence is apparently higher among Turkish, Middle-Eastern, North African, and South-East Asian patients than in European patients [136,137,[140][141][142][143][144]. Recently, in an extensive review by Martinez-Ramoz and coll., 70 studies reporting idiopathic granulomatous mastitis were identified, involving 3060 patients with a median age of 36 years old.…”
Section: Granulomatous Mastitis Associated With Other Autoimmune Disementioning
confidence: 99%
“…These elements, which suggest the key role of autoimmunity in the pathophysiology of IdGM, are sustained by the therapeutic strategies used. Indeed, although wide surgical excision still remains a therapeutic option [142,148,159], patients with recurrent IdGM have a good clinical response after steroid and immunosuppressive treatment [148,160]. A large retrospective series of 206 Iranian women of childbearing age (22-40 years old) highlights the positive effect of immunosuppressive treatment [138].…”
Section: Granulomatous Mastitis Associated With Other Autoimmune Disementioning
confidence: 99%